Human serum albumin nanoparticles as an efficient noscapine drug delivery system for potential use in breast cancer: preparation and in vitro analysis - Safaa Sebak (Dove Medical Press, 2010)
Safaa Sebak, Maryam Mirzaei, Meenakshi Malhotra, Arun Kulamarva, Satya PrakashBiomedical Technology and Cell Therapy Research Laboratory, Department of Biomedical Engineering, Faculty of Medicine, McGill University, Montreal, Quebec, CanadaAbstract: Drug delivery systems such as nanoparticles can provide enhanced efficacy for anticancer agents. Noscapine, a widely used cough suppressant for decades has recently been shown to cause significant inhibition and regression of tumor volumes without any detectable toxicity in cells or tissues. Nanoparticles made of human serum albumin (HSA) represent promising strategy for targeted drug delivery to tumor cells by enhancing the drug’s bioavailability and distribution, and reducing the body’s response towards drug resistance. In the present study, we report for the first time the incorporation and delivery of noscapine-loaded HSA nanoparticles to tumor cells. The nanoparticles were designed and optimized to achieve a particle size in the range of 150–300 nm with a drug-loading efficiency of 85%–96%. The nanoparticles were evaluated in vitro for their anticancer activity and efficacy on breast cancer cells.Keywords: HSA, encapsulation, microcapsule, nanomedicine, nanotechnology, tumor volumes